Mahathir Mohamad as a World-Class Leader: A View from The Great Man Theory of Leadership - Razali, Nurul Aimi; Jaes, Lutfan; Mohamad Suhaimy, Khairul Azman; Ani, Fauziah; Nordin, Shah Rul Anuar; Sabtu, Muhamad Helmy; Hanapi, Mohd Shukri; Othman, Muhammad Fuad; Veloo, Ganesan; Mat Ariffin, Fazni (Journal of Techno-Social, 2022)
Mahathir Mohamad’s leadership as the Prime Minister of Malaysia is an example of excellent leadership. His stint is peculiar as he is the longest-serving leader in the world and the oldest Prime Minister to ever lead a country. The impact of his leadership establishes his reputation as an outstanding leader as supported by the Great Man Theory of Leadership. As an effort to comprehend his leadership excellence, this study examined Mahathir’s leadership through the lens of the Great Man Theory of Leadership, which elevates leadership based on extraordinary achievements and considers the leader to be born a leader. The research was conducted by using a narrative review approach. Data were gathered qualitatively using thematic analysis, from secondary sources including academic journals, dissertations, books, and published articles pertaining to the topic of Mahathir’s leadership. The results found that his leadership approach is indeed aligned with the underlying elements of the Great Man Theory of Leadership, namely charismatic, intelligent, politically skilled, and wise. Past studies reported that Mahathir possesses the quality of being visionary, trustworthy, authentic, resourceful, pragmatic, people-oriented, good communication skills, highly ethical, and core value-based, thus strengthening his premise as an outstanding leader. His excellence in leading the country has been proven beneficial to both Malaysia and its people while the attention that he received from the international community further reinforced his relevance and influence at both the local and international levels. It is indeed a pride for Malaysia as a Southeast Asia country to have a world-class leader.